The effect of additional chlorhexidine and/or ethanol on the bond strength of universal adhesives. Issue 4 (16th February 2021) - Kaynar, Zeynep Buket; Kazak, Magrur; Donmez, Nazmiye; Dalkilic, Evrim Eliguzeloglu
Abstract: The aim of this study was to evaluate the effect of chlorhexidine and/or ethanol application on the bond strength of two universal adhesive systems. 36 extracted human teeth were used in this study. Standard Class I cavities (4 × 3 × 3mm) were prepared and divided into two groups according to the adhesive systems used. Each group was subdivided into three subgroups to be treated with chlorhexidine, ethanol, or unexposed to any solution. Group I; Universal bond I was applied without any treatment. Group II; 2% chlorhexidine was applied, before the application of universal bond I. Group III; 100% ethanol was applied, before the application of universal bond I. Group IV; Universal bond II was applied without any treatment. Group V; 2% chlorhexidine was applied, before the application of universal bond II. Group VI; 100% ethanol was applied, before the application of universal bond II. Then, teeth were restored with a nano-hybrid resin composite then subjected to thermo-cycling (10, 000 cycles, 5–55 °C). All teeth were exposed to 50, 000 cycles of loading in a chewing simulator. Twelve sticks from each group were obtained using a cutting machine. Sticks were subjected to a microtensile bond strength. After procedures, fractured surfaces were observed under a stereomicroscope to determine the mode of failure. Hybrid layer of each group was evaluated under a scanning electron microscope (SEM). Data were submitted to the Kruskal Wallis test. Significance level was set at 5%.No statistically significant differences were shown in all groups ( p > 0.05). The lowest bond strength value was obtained in group II (9.76), the highest bond strength value was determined in group IV (20.57). The study concluded that additional chlorhexidine or ethanol treatment may not influence directly the bond strength of universal adhesives when using a single-step self etch mode of universal adhesives.